Development of Digital Electronics Practicum Modules on Logic Gates - Merianti Merianti; Nehru Nehru; Wawan Kurniawan (Edumaspul: Jurnal Pendidikan, 2023)
Digital electronics practicum is one of the subjects studied in the Physics Education Study Program at the University of Jambi. Based on the initial needs questionnaire, it was found that 88% of students stated the logic gate material, including material that was difficult to learn. The purpose of this research is to develop a practicum module on logic gates material. This research is development research that uses the ADDIE development model and is carried out up to the evaluation stage. The subjects of this study were 35 students of Physics Education FKIP Jambi University class of 2017. The instruments used were media and material validation questionnaires as well as student perception questionnaires. The Analyze phase was used to obtain data, namely that there was no review of the material in the practicum guide previously used and work procedures that were difficult to understand. Next is the Design stage, the printed module design is made using the Microsoft Office Word 2010 program. The Develop stage, the development of direct instruction-based digital electronics modules on logic gates material. The results of the validation of the practicum presentation were 87% in the very good category and the results of the material validation were 62% in the good category. As for the results of student perceptions of the product being developed is 89% with a very good category. The advantage of the product being developed is that the experimental procedures are arranged systematically according to the Direct Instruction syntax. Based on these results it can be concluded that the digital electronics practicum module on logic gate material is suitable for use as a learning medium that can be used in the implementation of learning digital electronics practicum courses.